Ball-like nickel hydroxide nanoparticles: Electro-synthesis, characterization, and application. (March 2021) - Bagheri, Fathollah; Mosivand, Saba
Abstract: Ball-like nickel hydroxide nanostructures were synthesized using electro-crystallization method. The synthesis was carried out in an electrolytic cell containing two nickel electrodes, and an aqueous solution of C4 H12 Cl as supporting electrolyte. The effect of applied voltage on morphology, structure, and magnetic properties of the products were studied using XRD, FT-IR, SEM/EDX, TEM, and VSM. The XRD patterns confirm the formation of hexagonal structure of Ni(OH)2 without any impurities. Based on FT-IR results the amine molecules present at the surface of particles. The SEM images show that the products have ball-like shape. Each nickel hydroxide ball composed of the small nanoparticles. The mean particle size increases from ∼9 nm to ∼50 nm by increasing the applied voltage from 8 V to 26 V. The ability of electro-synthesized nickel hydroxide nanostructures on removal of cobalt and cadmium from laboratory water and real water of Khorram-rood, Seimareh, and Kashkan rivers in Iran, has been investigated. The AAS data show that the removal efficiency of heavy metals from real water is higher than laboratory water. Based on these results we could successfully remove 100 % of cadmium and 85.8 % of cobalt from real water samples.